Réponses

  • Utilisateur Brainly
2013-06-13T21:29:18+02:00

Ex 3:

1) A=7/11*2/7-(5/3-1)²

       =2/11-(2/3)²

       =2/11-4/9

       =18/99-44/99

       =-26/99

 

2) B=(24*10^(-7)*3*(10^3)^2)/(6*10^(-3))

       =24*3/6*10^(-7-6+3)

       =12*10^(-10)

       =1,2*10^(-11)

 

3) C=2√5+2√125-7√45

        =2√5+2*5√5-7*3√5

        =-9√5

 

Ex 4:

E=(3x-1)²-(3x-1)(2x+3)

 

1) E=9x²-6x+1-(6x²+9x-2x-3)

       =9x²-6x+1-6x²-7x+3

       =3x²-13x+4

 

2) x=√2

donc E=3*2-13√2+4

             =10-13√2

 

3) E=(3x-1)(3x-1-2x-3)

       =(3x-1)(x-4)

 

4) E=0

donc (3x-1)(x-4)=0

donc 3x-1=0 ou x-4=0

donc x=1/3 ou x=4

2013-06-13T22:16:37+02:00

A)

7/18 x 2/7 =14/126

(5/3 - 1) =(5/3 - 3/3)=2/3

(2/3)²=4/9

4 x 14 =56

9 x 14 =126

donc =56/126

14/126 - 56/126 =- 42/126

- 42/126 divisé par 6 =-6/9

-6/9 divisé par 3 =-2/3